Emissões de títulos no mercado de capitais e variáveis macroeconômicas: evidências para o Brasil - Cortez, Shirley Andrade Teixeira (Brasil, 2023)
Capital market emissions in Brazil contribute to economic growth, in view of its important and growing participation as a source of capitalization by Brazilian companies. In this sense,this study sought to analyze the impact of macroeconomic variables on funding via the Brazilian capital market for the period from 2004 to 2021, in addition to showing the allocations of funds from funding via debentures. Ordinary least square (MQO) models were estimated to determine how macroeconomic variables affect emissions in the capital market. In addition, a literature review was conducted on the history and functioning of the financial market, national financial system and capital market. The results indicate that capital market funding is directly affected by some macroeconomic variables.